Canada : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This paper assesses the impact of high household debt on economic volatility in Canada. The debt per se may not necessarily be a risk for economic activity; it can amplify other shocks as well. A few studies have emphasized the link between the growth of household debt before 2007 and the severity of the Great Recession. Economies with debt tend to experience more severe housing busts and recessions. If household debt ratios are not stabilized, the vulnerability of the Canadian economy is likely to be high.